Website Development of Indonesian Culture Teaching Materials based on the International Baccalaureate (IB) Curriculum for BIPA SMA - Pitra Ramadhani; Yulianeta Yulianeta; Nuny Sulistiany Idris (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2023)
With an international curriculum, Sekolah Satuan Pendidikan Kerja Sama (SPK) brings a new perspective to BIPA learning. With limited reference to BIPA materials, this situation is a challenge. The aim of this research is to provide Google Sites-based teaching resources for Indonesian culture. The ADDIE model (analysis, design, development, implementation, and evaluation) is used in this study, which is descriptively analyzed. Respondents in this study were students, subject teachers, media specialists, and material experts. The research instrument used were tested for validity and reliability, including a feasibility test questionnaire, practicality test, and validity test (r number > 0.70). The Indonesian cultural resources for the Indonesian B course came up to have been developed by the requirements of the Language B Policy of the IB DP Curriculum. The policy consists of five themes: identity, experience, human ingenuity, social organization, and sharing the planet. The Google Sites materials consist of a home menu, learning materials, exercises, portfolios, and reflections. The materials are checked for feasibility, practicality, and effectiveness. According to test results, Indonesian cultural materials are considered highly relevant and appropriate (91.1%), efficient (87.8%) and highly effective (86.7%) in conducting BIPA learning. It is hoped that the page-based product of the Indonesian cultural materials Google site will be a reference for BIPA learning.